G-quadruplex formation in the Oct4 promoter positively regulates Oct4 expression - Renčiuk, Daniel; Ryneš, Jan; Kejnovská, Iva; Foldynová-Trantírková, Silvie; Andäng, Michael; Trantírek, Lukáš; Vorlíčková, Michaela (Biochimica et biophysica acta. Gene regulatory mechanisms, 2017)
The Oct4 gene codes for a transcription factor that plays a critical role in the maintenance of pluripotency in embryonic and cancer stem cells. Its expression thus has to be tightly regulated. We performed biophysical characterization of the promoter region using a combination of UV absorption, CD, and NMR spectroscopies, native PAGE and chemical probing, which was followed by functional studies involving luciferase reporter assays performed in osteosarcoma and human embryonic stem cell lines. We have shown that the evolutionarily conserved G-rich region close to the Oct4 transcription start site in the non-template strand forms a parallel G-quadruplex structure. We characterized its structure and stability upon point mutations in its primary structure. Functional studies then revealed that whereas the wild type quadruplex sequence ensures high reporter gene expression, the expression of mutated variants is significantly decreased proportionally to the destabilizing effect of the mutations on the quadruplex. A ligand, N-methyl mesoporphyrin IX that increases the stability of formed quadruplex rescued the reporter expression of single-mutated variants to the level of wild-type, but it has no effect on a mutated variant that cannot form quadruplex. These data indicate that the quadruplex acts as a strong, positive regulator of Oct4 expression and as such it might serve as a potential target for therapeutic intervention.
Keywords: nádorové buněčné linie; cirkulární dichroismus; Guanine quadruplex; osteosarkom; Octamer Transcription Factor-3; reportérové geny; Promoter Regions, Genetic; Circular dichroism; mutace; Cell Line, Tumor; Transcription regulation; Embryonic Stem Cells; mesoporfyriny; embryonální kmenové buňky; magnetická rezonanční tomografie; Luciferase reporter; Magnetic Resonance Imaging; Genes, Reporter; G-kvadruplexy; Mutation; Humans; Circular Dichroism; oktamerní transkripční faktor 3; Transcription Initiation Site; Oct4; promotorové oblasti (genetika); Osteosarcoma; počátek transkripce; G-Quadruplexes; Human embryonic stem cells; Mesoporphyrins; lidé